Hubungan Pengetahuan tentang Lalat dengan Perilaku Pengendalian Lalat pada Penjamah Makanan di Kawasan Kuliner Wisata Pantai Depok Bantul - Rustiawan, Asep; Egitasari, Rismala (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2025)
Houseflies are the primary vectors for the spread of pathogens that cause foodborne diseases. Flies are commonly found on open food displays, such as those found in the coastal culinary tourism area of Depok Bantul. Food handlers play a crucial role in maintaining food hygiene. Their knowledge is a key factor influencing their behavior in fly control. This study aims to measure the knowledge about flies and its relationship with fly control behavior among food handlers in the Depok Bantul beach tourism area. The study used a Cross-sectional design involving 80 food handlers selected through purposive sampling. The instrument used was a closed-ended questionnaire that had been tested for validity and reliability. Data analysis was performed using the Chi-square test with a significance level of 0.05. The results showed that 51.25% of respondents had a high level of knowledge about flies, and 56.25% demonstrated good fly control behavior. Statistical tests showed a significant relationship between knowledge and fly control behavior (p=0.004; PR=4.364; CI 95%=1.696–11.229). Food handlers with high knowledge tended to have better fly control behavior. These findings emphasize the importance of ongoing education in raising awareness and preventive measures against the dangers of flies as disease vectors.